Changes in social inequality with respect to health-related living conditions of 6-year-old children in East Germany after re-unification - Ranft Ulrich; Krämer Ursula; du Prel Xianming (BMC, 2005)
Abstract Background Since Germany re-unified in 1990, substantial social and economic changes have happened in East Germany, the former socialist German Democratic Republic (GDR). The aim of this study was to investigate the influence of these socio-economic changes in East Germany on the association between social status, measured by parental educational level, and health-related living conditions of children during the ten-year period after re-unification. Methods In total, 25,864 6-year-old school beginner children (51.2% male and 48.8% female) participated in cross-sectional studies which have been repeated every year from 1991 to 2000 in East Germany. Parental educational level as a social indicator was the independent variable. Dependent variables included not employed parents, small living space and health-related living conditions (e. g. damp housing, single oven heating and living at busy road). The relationships were described by odds ratios using logistic regression. Results A large overall effect of parental educational level on health-related living conditions was observed. The time trends showed that the situation regarding small living space, damp housing conditions and single oven heating improved from 1991 to 2000, while regarding not employed parents (1996-2000) and living at busy road (1991-2000) did not, but even deteriorated. 6-year old children with low parental educational level, who lived at the time of re-unification, were often under damp housing conditions and with single oven heating at homes. Nevertheless, this social inequality has almost vanished ten years later. In contrast, we found an increasing gap between low and high parental educational level with respect to the proportion of parents who were not employed (22%: 4% gain), or lived under cramped housing conditions (22%: 37% reduction), or close to a busy road (7% gain: 2% reduction). Conclusion The social inequalities which already existed under the socialist system in East Germany persisted in the system of social market economy between 1991 and 2000. 6-year-old children from families with the lowest social status were living under the worst domestic conditions (e. g. living at busy road, having damp housing conditions, single oven heating and small living space) and for some conditions (e. g. living at busy road and having small living space) the gap betweenlow and high social status was even bigger in 2000 than in 1991.